The E2F family and transcriptional control of the mammalian cell cycle - Dynlacht, Brian (Henry Stewart Talks, 2007)
Complex and diverse roles of E2F family members, Interaction with tumour repressor proteins, Interaction with chromatin modifying enzymes, Study using microarray technology and chromatin immunoprecipitation, Novel features of cell cycle dependent transcription, Roles in regulating G1-to-S transition, mitosis, differentiation, and apoptosis
Archived at 2016/06/22